Revolution and Witchcraft The Code of Ideology in Unsettled Times - Chang, Gordon C. (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Dr. Chang expands the utility of micro-level discourse analysis techniques in his investigation of three macro-level idea systems: witch hunt social movements, Mao-era revolutionary campaigns, and the US War on Terror. The result is a fresh understanding of each system, original insight into their historical similarities, and an intriguing display of the strategies that systems leaders deploy to retain power." -Hugh B. Mehan, Professor Emeritus of Sociology, University of California, San Diego "This bold and stunning book excavates the ideological codes that sustain social and political movements across time, space, and cultures. Ranging from early modern European witchcraft to the Chinese cultural revolution and the US War on Terror, this comparative study provides illuminating insights and reflections on how new ideas morph into social movements with rare and extreme political consequences. It is a stimulating and informative 'must read' for scholars of socialand political philosophy and students of the sociology of knowledge." -Bennetta Jules-Rosette, Distinguished Professor of Sociology and Director of African and African-American Studies Research Center, University of California, San Diego Ideas influence people. In particular, extremely well-developed sets of ideas shape individuals, groups, and societies in far-reaching ways. This book establishes these "idea systems" as an academic concept. Through three intense episodes of manipulation and mayhem connected to idea systems-Europe's witch hunts, the Mao Zedong-era "revolutions," and the early campaign of the U.S. War on Terror-this book charts the cognitive and informational matrices that seize control of people's mentalities and behaviors across societies. Through these, the author reaches two conclusions. The first, that we are all vulnerable to the dominating influence of our own matrices of ideas and to those woven by others in the social system. The second, that even the most masterful manipulators of idea programs may lose control of the outcomes of programmatic manipulation. Amongst this analysis, sixty-plus central conceptual terminologies are provided for readers to analyze multiform idea systems that exist across space, time, and cultural contexts. Gordon C. Chang (郑志达) is Associate Professor of Sociology at Western Illinois University, USA. .